1973
DOI: 10.1111/j.0954-6820.1973.tb10614.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytostatic Treatment of Glomerular Diseases

Abstract: Forty‐six patients with chronic glomerular diseases have been treated with azathioprine for up to 84 months. The importance of the variables sex, age, clinical diagnosis, histological glomerular changes, arterial hypertension, treatment with prednisone and initial values of serum creatinine and proteinuria was investigated. In 22 patients the renal state as estimated by serum creatinine, proteinuria and urinary sediment was normalized or improved. The renal state was unchanged in 9 patients and deteriorated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1973
1973
1999
1999

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Because of the side-effects the indications for cytostatic drugs in renal glomerular disease are limited. In previous studies we have demonstrated a beneficial effect of 16 weeks of treatment with cyclophospharnide on glomerulonephritis as evaluated by Screatinine and proteinuria (1). The improvement occurred primarily within the first 4 weeks.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Because of the side-effects the indications for cytostatic drugs in renal glomerular disease are limited. In previous studies we have demonstrated a beneficial effect of 16 weeks of treatment with cyclophospharnide on glomerulonephritis as evaluated by Screatinine and proteinuria (1). The improvement occurred primarily within the first 4 weeks.…”
mentioning
confidence: 77%
“…Consequently, the null hypothesis as well as the alternative hypothesis has to be defmed. The results from our previous study (1) were used for that purpose. In Table II empiric distributions for improved, unchanged, and deteriorated are listed for cyclophosphamide-treated and for placebo-treated patients from the previous study.…”
Section: Trial Procedures and Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The histological classification included the following groups: minimal changes, epimembranous, proliferative, exudative, extracapillary, membranoproliferative, lobular, segmental-focal, and unclassified GN. The basis for this classification and the technical procedures have been presented in a previous paper (1). Immunofluorescence and electron microscopy findings were not included in the classification procedure, as these investigations were not systematically performed.…”
Section: Methodsmentioning
confidence: 99%